Integrasi Face Detector dengan IoT untuk Sistem Keamanan Pintu Rumah Pintar - Jaka Pramana, Felista; Pujiastutik, Rini (Fakultas Teknik UMRI, 2026)
The high incidence of home burglaries in Indonesia has driven the need for the development of more modern and effective security systems compared to conventional manual locks, which still have many weaknesses. This research develops an Internet of Things (IoT)-based home door security system by implementing face detection as the primary authentication method. The system is designed using an ESP32 as the main controller, integrated with an ESP32-CAM for face recognition, a 4x4 keypad as a PIN input medium, an SW-420 vibration sensor to detect forced break-in attempts, a buzzer as a warning alarm, and a solenoid door lock as the door-opening and locking actuator. The system operates with two authentication mechanisms, namely face recognition and PIN input, thereby providing layered security. If the authentication process is successful, the door will open automatically and the system will send a notification reading